An empirical study of corporate social and environmental communication - Nurhayati, Ratna (Curtin University, 2014)
The theoretical contribution of this study is the successful testing of legitimacy theory in the context of an emerging economy. This study finds a low extent (13.57%) of social (10.44%) and environmental (17.98%) disclosure (SED) practices of Indian textile and apparel listed firms over 2010-2012. Firm size (+), brand development (+), audit committee independence (+), profitability (+), CEO duality (-) and award obtained (+) are significant predictors of the extent of SED. Economically, firm size and brand development are major determinants.